Visceral leishmaniasis in a canine: Case report - de Sousa Brito, Aishá Ingrid de Sousa Brito (Pubvet, 2021)
The Visceral Leishmaniasis or Kala-azar is a zoonosis that has spread quickly in Bahia because of the urbanization process. The case report has the objective of defining the importance of diagnosis and treatment of the disease in dogs, showing from the illness identification by the veterinary doctor, laboratory tests, cytological and imaging. The study was conducted in a 24 hours veterinary hospital, located in the city of Vitória da Conquista, in Bahia’s countryside. The patient was a canine, male and fertile, American Staffordshire Terrier breed of nine months and fourteen days old, weighing 22kg, with rabies, viral multiple and vermifugation vaccines up to date. After the confirmation of clinical suspicion through the Polymerase Chain Reaction - PCR for leishmania sp, by fine needle aspiration puncture and hematological and imaging exam, the animal had fully support for symptom control and the leishmaniasis treatment protocol was initiated with the association of domperidone, milteforan, allopurinol, in addition to the beginning of the vaccination protocol with the leishtec vaccine and the use of repellent collars.
Keywords: Kala-aza; dogs; epidemiology